ChemInform Abstract: Stereoselective Total Synthesis of Amicoumacin C. Issue 29 (July 2015) - Suzuki, Tomomi; Nagasawa, Tomohiro; Enomoto, Masaru; Kuwahara, Shigefumi
Abstract The 13‐step synthesis of amicoumacin C (I) is achieved in 17% overall yield from l‐phenylalanine.